Synthesis and characterization of polyethylene glycol mediated silver nanoparticles by the green method - Shameli, Kamyar; Ahmad @ Ayob, Mansor; Jazayeri, Seyed Davoud; Sedaghat, Sajjad; Shabanzadeh, Parvaneh; Jahangirian, Hossein; Mahdavi, Mahnaz; Abdollahi, Yadollah (MDPI AG, 2012)
The roles of green chemistry in nanotechnology and nanoscience fields are very significant in the synthesis of diverse nanomaterials. Herein, we report a green chemistry method for synthesized colloidal silver nanoparticles (Ag NPs) in polymeric media. The colloidal Ag NPs were synthesized in an aqueous solution using silver nitrate, polyethylene glycol (PEG), and β-d-glucose as a silver precursor, stabilizer, and reducing agent, respectively. The properties of synthesized colloidal Ag NPs were studied at different reaction times. The ultraviolet-visible spectra were in excellent agreement with the obtained nanostructure studies performed by transmission electron microscopy (TEM) and their size distributions. The Ag NPs were characterized by utilizing X-ray diffraction (XRD), zeta potential measurements and Fourier transform infrared (FT-IR). The use of green chemistry reagents, such as glucose, provides green and economic features to this work.